Promising management strategies to improve crop sustainability and to amend soil salinity - Mishra, Ajay Kumar; Das, Rajeswari; George Kerry, Rout; Biswal, Bisworanjita; Sinha, Trisha; Sharma, Sheetal; Arora, Pooja; Kumar, Mukesh (Frontiers Media, 2023)
By affecting 10% of the world’s total arable land, soil salinity has become a potential threat to feeding the exploding population. As per the current scenario, among 1,125 million hectares of salt-affected land, nearly 76 million hectares are seriously affected due to human-induced salinization. Due to soil salinization, crop productivity is being hampered. In order to enhance productivity, there is an urgent need to shift from traditional methods to advanced 3E (efficient, economic, and environmentally sound) technology for soil salinity reclamation and management to achieve better soil health and sustainable crop production. The detailed mechanism of salt interference with various pathways involved in plant growth and development needs to be understood. This article critically reviews the mechanism of harmful salt interference with nutrient dynamics in soil and various physiological pathways involved in crop growth to apply various soil-oriented (crop residue management, biochar application, and agroforestry system) and plant-oriented [plant growth-promoting microbes (PGPMs), plant growth regulators, and nanotechnology] promising reclamation and rehabilitation approaches to mitigate its hazardous effect on soil salinity. The monitoring and assessment of salt-affected soils through remote sensing (RS) and geographical information systems (GISs) are pivotal in the management and framing of long-term policies to confront alarming threats to crop productivity and sustainability. This study provides an insight into recent developments in soil salinity management and proposes futuristic solutions that could ameliorate soil salinity to attain crop sustainability under adverse environmental conditions.